Toward a New Definition of Shared Prosperity : A Dynamic Perspective from Three Countries - Dang, Hai-Anh H.; Lanjouw, Peter F. (World Bank, Washington, DC, 2015)
This paper proposes a new measure of growth in shared prosperity, based on shifts in population shares of different income groups over time. This measure complements the definition of shared prosperity recently proposed by the World Bank in which income growth of the bottom 40 percent is examined. The new measure’s strengths arise from its close ties to countries’ national poverty lines and poverty measures, its focus on inclusion of the vulnerable population, and its identification of a population segment that is neither poor nor at significant risk of falling into poverty. The paper also offers a typology of scenarios for tracking shared prosperity under this measure. It provides illustrative examples using survey data from India, the United States, and Vietnam for the mid-to-late 2000s. Estimation results comparing the two approaches with measuring the evolution of shared prosperity are qualitatively consistent, and suggest that during this period, Vietnam enjoyed the greatest expansion in shared prosperity, followed by India and then the United States.